Comparative study of Cronobacter identification according to phenotyping methods. Issue 1 (December 2016) - Jackson, Emily; Forsythe, Stephen
Abstract Background Microbiological criteria applied to powdered infant formula (PIF) require the absence of allCronobacter spp. Consequently, misidentification of isolates from finished products can lead to significant financial losses for manufacturers and could increase the risk of neonatal infection. Biochemical identification of suspect isolates using commercially available test panels is recommended for use by PIF manufacturers by both the US FDA and ISO standard methods forCronobacter species; however, phenotyping can be unreliable, particularly for a genus such asCronobacter where the taxonomy has been subject to frequent changes. This study compared the predicted identification by commonly used phenotyping kits (API20E and ID32E) for over 240 strains ofCronobacter from diverse sources, which had been identified using DNA sequence analysis. In 2015, the databases associated with the API20E and ID32E biochemical test panels were updated, including the recognition of theCronobacter genus. Thus, the identifications from multiple versions the databases were compared to each other and to identifications based on DNA sequencing methods. Results Using previous versions of the API20E database, 90.0 % of strains (216/240) resulted in a match for the species identification; however, version 5.0 produced matches for only 82.3 % of strains (237/288). Similarly, the update to version 4.0 in the ID32E database caused the percentage of matches to drop from 88.9 % (240/270) to 43.2 % (139/322). A smaller study showed that the Vitek GN system identified all 14 strains, belonging all sevenCronobacter species, as members of the 'C. sakazakii group, ' but also attributed three strains ofFranconibacter helveticus andF. pulveris to this group.In silco analysis of a PCR-based method targetingompA predicted that amplification would only occur withCronobacter species and this method may be a feasible alternative to biochemical phenotyping. Conclusions These results indicate that commercially available biochemical test panels are not sufficiently reliable for speciation ofCronobacter isolates. Although DNA-sequence based methods would be the more reliable approach; however, this is not currently feasible for many food microbiology laboratories. Instead, a previously published PCR-based method targetingompA is suggested as an alternative for identification ofCronobacter species based onin silico analysis.